Total and regional bone mass in female soccer players - Alfredson, H.; Nordstrom, P.; Lorentzon, R. (Calcified Tissue International, 1997)
This cross-sectional study investigated bone mass in female athletes participating in an impact-loading sport (soccer), and evaluated whether any changes in bone mass could be related to the type of weight-bearing loading and muscle strength. The group of soccer players consisted of 16 second-division female players (age 20.9 +/- 2.2 years) training for about 6 hours/week. The reference group consisted of 13 nonactive females (age 25.0 +/- 2.4 years) not participating in any kind of regular or organized sport activity. The groups were matched according to weight and height. Areal bone mineral density (BMD) was measured in total body, head, lumbar spine, femoral neck, Ward's triangle, trochanter, the whole femur and humerus, and in specific sites in femur diaphysis, distal femur, proximal tibia, and tibia diaphysis using dual X-ray absorptiometry. Isokinetic concentric peak torque of the quadriceps and hamstring muscles was measured using an isokinetic dynamometer. The soccer players had significantly (P < 0.05-0.01) higher BMD in the lumbar spine (10.7%), femoral neck (13.7%), Ward's triangle (19.6%), nondominant femur and humerus (8.2 and 8.0%, respectively), distal femur (12.6%), and proximal tibia (12.0%) compared with the nonactive women. There was no significant difference in muscle strength of the thigh between the two groups. In the nonactive group, muscle strength in the quadriceps and especially hamstrings, was correlated to BMD of the adjacent bones (whole femur, hip sites) and also to distant sites (humerus). In the soccer group, there were no correlations between muscle strength and BMD of the adjacent and distant bones. Soccer playing and training appears to have a beneficial effect on bone mass in young females, and it seems that there is a site-specific skeletal response to the type of loading subjected to each BMD site. Muscle strength in the thigh is not related to bone mass in female soccer players.